P256Research of the spot urine method in estimating 24-hour urinary sodium in hypertensive patients. (15th July 2014) - Xi, Y; Sun, N; Zhao, L; Wang, H; Chen, Y; Liu, X; Han, W
Abstract: Objective: To develop an equation to estimate 24-hour urinary sodium by using spot urine in Chinese hypertensive patients and explore its applicability. Methods A total of 510 hypertensive patients were recruited, including 340 cases set up by the new equation and 170 cases as the equation validation groups. 24-hour urinary sodium(24HUNa), 24-hour urinary creatinine(PRCr), spot urinary sodium(SUNa) and creatinine(SUCr) for two times were measured for creating an equation (SUN) predicted 24h urinary sodium by spot urine. And applicability of the equation were evaluated simultaneously. To examine the deviation, precision and accuracy of the equation, we compared the estimated values (e-24HUNa) and the measured values (r-24HUNa). Results: The improved equations (SUN) for predicting 24HUNa using spot urine were as follows: PRCr(mg/day) = 13.41× body weight(Kg) +14.49 × height(cm) – 12.22 × age – 1406.3; SMU (second morning spot urine): e-24HUNa = 34.12 × [(SUNa/SUCr)×PRCr]0.27; PM (late afternoon or early evening spot urine): e-24HUNa = 23.01×[(SUNa/SUCr)×PRCr]0.34. The equation showed smaller deviation and higher accuracy compared with Kawasaki's and Tanaka's method, especially when salt intake of patients was less than 12g/day, but was not suitable for patients whose salt intake was greater than 12g/day. Conclusions: The improved equation (SUN) showed a better applicability in estimating 24-hour urinary sodium excretion in Chinese hypertensive patients, with a small deviation and high precision and accuracy. The equation of SMU were more convenient to estimate 24h urinary sodium. It was suitable for hypertensive patients with salt intake less than 12g/day.